2014
DOI: 10.1126/scitranslmed.3007096
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3–Like 1 Suppresses Injury and Promotes Fibroproliferative Responses in Mammalian Lung Fibrosis

Abstract: Epithelial injury, alternative macrophage accumulation, and fibroproliferation coexist in the lungs of patients with idiopathic pulmonary fibrosis (IPF). Chitinase 3–like 1 (CHI3L1) is a prototypic chitinase-like protein that has been retained over species and evolutionary time. However, the regulation of CHI3L1 in IPF and its ability to regulate injury and/or fibroproliferative repair have not been fully defined. We demonstrated that CHI3L1 levels were elevated in patients with IPF. High levels of CHI3L1 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
184
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 184 publications
(195 citation statements)
references
References 63 publications
11
184
0
Order By: Relevance
“…First, studies from our laboratory have demonstrated that oxidant injury is a powerful inhibitor of CHI3L1 and that if oxidant inhibition of CHI3L1 is prevented, oxidant injury and lung epithelial cell apoptosis are abrogated (36). Similar results were found in experiments with bleomycin (27). This suggests that a decrease in CHI3L1 appears to be a prerequisite for agents such as hyperoxia or bleomycin to induce the acute and severe tissue injury and alveolar epithelial cell death responses that they generate.…”
Section: Il-13rα2 Membrane Expression Is Decreased In Hps Lung Tissuessupporting
confidence: 74%
See 4 more Smart Citations
“…First, studies from our laboratory have demonstrated that oxidant injury is a powerful inhibitor of CHI3L1 and that if oxidant inhibition of CHI3L1 is prevented, oxidant injury and lung epithelial cell apoptosis are abrogated (36). Similar results were found in experiments with bleomycin (27). This suggests that a decrease in CHI3L1 appears to be a prerequisite for agents such as hyperoxia or bleomycin to induce the acute and severe tissue injury and alveolar epithelial cell death responses that they generate.…”
Section: Il-13rα2 Membrane Expression Is Decreased In Hps Lung Tissuessupporting
confidence: 74%
“…Importantly, the majority the first time to our knowledge, that this binding plays a critical role in CHI3L1-induced fibroproliferative repair. In accordance with the importance of M2 macrophages and fibroblast activation in fibrogenesis (27), these studies also demonstrate that CRTH2 plays a key role in CHI3L1-induced M2 macrophage differentiation and allow for the speculation that CRTH2 also plays a role in fibroblast proliferation and activation and other fibroproliferative events.…”
Section: Il-13rα2 Membrane Expression Is Decreased In Hps Lung Tissuessupporting
confidence: 48%
See 3 more Smart Citations